Pengaruh Pemahaman Pajak, Tarif Pajak, Sanksi Pajak, Penerapan E-Filing Terhadap Kepatuhan Wajib Pajak UKM - Roechyati Yulianti; Sartika Wulandari (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
With a very large number of business actors, through taxes, SMEs play a significant role in increasing state revenue, ironically the tax contribution from SMEs to national tax revenue is still relatively low. This study was conducted to measure how far tax knowledge, tax rates, tax sanctions, and the ease of implementing e-filing, affect the behaviour of SME tax obligations in fulfilling their tax responsibilities. This research adopts a quantitative approach and uses the theory of planned behaviour to explain the phenomenon under study. The research sample consists of 109 randomly selected SME respondents, where the sample size is determined based on statistical calculations using the Slovin formula. By conducting multiple linear regression analysis to evaluate the interrelationship of various variables, using SPSS version 25. According to the findings, respondents' sufficient understanding of tax provisions, the application of sanctions, and the use of e-filing significantly contributed to the increase in compliance, while the tax rate variable did not show a significant relationship.